Chain cleavage mechanism of palm kernel oil derived medium-chain-length poly(3-Hydroxyalkanoates) during high temperature decomposition - Sin, M.C.; Gan, S.N.; Annuar, M.S.M.; Tan, I.K.P. (2011)
Medium-chain-length poly(3-hydoxyalkanoates) (mcl-PHAs) are natural polyesters having the molecular formula of similar to OCHR-CH(2)-COO similar to(n) In, composed of monomers each having 6 to 14 carbon atoms, with relatively bulky alkyl pendant group. They are primarily synthesized by fluorescent pseudomonads under unbalanced nutrient availability as carbon and energy storage compounds. From thermogravimetic analysis, the mcl-PHAs produced from Pseudomonas putida grown on palm kernel oil showed a drastic decomposition at temperature above 195 degrees C. An increase of HO-CHR similar to similar to terminals was observed when the mcl-PHAs were thermally decomposed at 160-180 degrees C, which was presumably due to the hydrolytic chain cleavage initiated at -COO-CHR similar to similar to, the main skeletal bonds of the biopolyester. At 190 degrees C, molecules with RCH CH similar to similar to were also observed as minor decomposition products from the FTIR and NMR measurements and this could be probably due to the dehydration of HO-CHR similar to groups of hydroxyl acids, producing terminally unsaturated oligomers. These observations were consistent with the detection of three new unsaturated monomers: C(4:1), C(6:1) and C(8:1) in the methanolyzed mcl-PHAs in gas chromatography analysis. (C) 2011 Elsevier Ltd. All rights reserved.